Effect of Hatha yoga on anxiety: a meta‐analysis. Issue 3 (August 2016) - Hofmann, Stefan G.; Andreoli, Giovanbattista; Carpenter, Joseph K.; Curtiss, Joshua
Abstract: Objective: Some evidence suggests that Hatha yoga might be an effective practice to reduce anxiety. To examine the effect of Hatha yoga on anxiety, we conducted a meta‐analysis of relevant studies extracted from PubMed, PsycINFO, the Cochrane Library, and manual searches. Method: The search identified 17 studies (11 waitlist controlled trials) totaling 501 participants who received Hatha yoga and who reported their levels of anxiety before and after the practice. We estimated the controlled and within‐group random effects of the practice on anxiety. Results: The pre–post within‐group and controlled effect sizes were, Hedges' g = 0.44 and Hedges' g = 0.61, respectively. Treatment efficacy was positively associated with the total number of hours practiced. People with elevated levels of anxiety benefitted the most. Effect sizes were not moderated by study year, gender, presence of a medical disorder, or age. Although the quality of the studies was relatively low, the risk of study bias did not moderate the effect. Conclusion: Hatha yoga is a promising method for treating anxiety. However, more well‐controlled studies are needed to compare the efficacy of Hatha yoga with other more established treatments and to understand its mechanism.